Pemikiran Hakim dalam Hukuman Mati Kejahatan Narkotika: Perspektif Hak Asasi Manusia dan Hukum Islam - Fikri, Fikri; Saidah, Saidah; Aris, Aris; Wahidin , Wahidin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
This study aims to explain the thoughts of judges in the death penalty for narcotics crimes with the relevance of human rights and Islamic law. The application of the death penalty is a very urgent problem, because in narcotics crimes it is referred to as an extraordinary crime. This study is a qualitative research with a descriptive-critical analytical method. The results of the study show that the death penalty does not contrast with human rights for narcotics offenders, especially in Islamic law including hirabah as an extraordinary crime regarding narcotics crimes which can deprive other people of life with absolute rights that must be defended and protected by the state. The judge's opinion refuses to put down human rights if it hinders the imposition of capital punishment, the abuse of narcotics that imposes a death penalty is in line with Islamic law and the Constitutional Court's decision regarding constitutional review is not contrary to human rights, the death penalty cannot be abolished, but is maintained according to law Islamic law and law, because the death penalty is not an opponent of human rights, but a supporter of human rights in the right to life and human life.